IMPLEMENTASI MANAJEMEN KEBERSIHAN CLEANING SERVICE TERHADAP KUALITAS LINGKUNGAN BELAJAR DI GEDUNG FTK UIN ALAUDDIN MAKASSAR: STUDI KUALITATIF DESKRIPTIF - Hasan, Syarah Ummy; Nasir, Muhammad Adithya Putra; Al Muawwal, Muhammad Yudi; Binti Abdullah, Khusaila; Suarga, Suarga (Department of Islamic Education Management, 2026)
This study aims to analyze the implementation of cleanliness management carried out by the cleaning service staff at the Faculty of Tarbiyah and Teacher Training (FTK), Alauddin State Islamic University of Makassar, and to examine its impact on the quality of the learning environment. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews with two students, one cleaning service staff member, and one cleaning coordinator, supported by observations and documentation. The findings indicate that the cleanliness management system has implemented the management functions of planning, organizing, actuating, leading, controlling, and evaluation, thereby contributing to the creation of a clean, comfortable, and conducive learning environment. However, improvements are still needed in documentation, strategic planning, and evaluation systems to enhance the effectiveness and sustainability of cleanliness management. The novelty of this study lies in its analysis of cleanliness management implementation based on management functions at the faculty level by positioning the cleaning service as a strategic actor in facility management to support the quality of the learning environment, an aspect that has received limited attention in previous studies. The findings are expected to serve as a reference for higher education institutions in developing a more systematic, well-documented, and sustainable cleanliness management system to improve the quality of educational services.